Glycoprotein IIb/IIIa inhibition reduces prothrombotic events under conditions of deep hypothermic circulatory arrest - Straub, Andreas; Azevedo, Ruben; Beierlein, Wolfram; Wendel, Hans P.; Dietz, Klaus; Ziemer, Gerhard (Thrombosis and Haemostasis, 2005)
Deep Hypothermic Circulatory Arrest (DHCA) is employed during thoracic aortic and congenital heart surgery, and can induce postoperative neurological damage probably caused by microthrombembolism. Hypothermia has been reported to induce platelet activation and aggregation. The platelet activation marker P-selectin mediates binding of platelets to leukocytes. Tirofiban and eptifibatide, short-acting inhibitors of the platelet fibrinogen receptor GP IIb/IIIa, have recently been shown to protect platelet function without increasing bleeding during heart surgery using cardiopulmonary bypass. The aim of this study was to investigate the effect of tirofiban and eptifibatide on platelets and platelet-leukocyte interaction under DHCA conditions in vitro.Platelet aggregation, binding of the GP IIb/IIIa activation specific antibody PAC-1, P-selectin expression as well as monocyte and granulocyte content of aggregates were investigated in un-stimulated and ADP-stimulated samples using flow cytometry. Tirofiban and eptifibatide inhibited massive platelet aggregation and PAC-1 binding which were induced by DHCA conditions. P-selectin expression was inhibited by tirofiban but increased by eptifibatide at hypothermia. Platelet-bound leukocytes were present in all samples. Eptifibatide increased granulocyte content of aggregates at hypothermia in ADP-stimulated samples. We conclude that under conditions of DHCA both tirofiban and eptifibatide inhibit platelet aggregation but have different effects on platelet P-selectin expression and platelet-leukocyte interaction. Application of a short-acting and non-activating GP IIb/IIIa inhibitor should be considered during DHCA in vivo to prevent occlusion of the microvasculature and subsequent organ damage.
Keywords: Platelet physiology; cell-cell interactions; coagulation inhibitors; platelet pharmacology